Knowing Words : Wisdom and Cunning in the Classical Traditions of China and Greece - Raphals, Lisa (Ithaca, NY : Cornell University Press, 2018)
For the Greeks, the craft of Odysseus and the wisdom of Athena were examples of metis, an elusive cast of mind that ranged from wisdom and forethought to craft and cunning. Although it informed many aspects of Greek society, metis was all but absent from the language of Greek philosophy. Invoking Indigenous Chinese debates, Lisa Raphals here examines the role and significance of metic intelligence in classical Chinese philosophy, literature, history, and military strategy. Raphals first examines the range of meanings of the Chinese word zhi. As with the Greek metis, the uses of zhi include "wisdom, " "knowledge, " "intelligence, " "skill, " "cleverness, " and "cunning." Drawing on parallels between the two traditions, she argues that, in China as in Greece, metic intelligence tacitly informed many aspects of cultural and social life. In China, these included views of the nature of knowledge and language, standards of personal and social morality, and theories of military strategy and statecraft. After surveying representative texts from the Warring States period, Raphals considers the function of metic intelligence as the dominant quality of central characters in two novels from the Ming dynasty, the Romance of Three Kingdoms and Journey to the West. Finally, she compares the treatment of themes of heroism and recognition in the Chinese and Greek narrative traditions. Knowing Words will be welcomed by sinologists, classicists, and scholars of comparative philosophy and literature.
Frontmatter -- Contents -- Foreword / Nagy, Gregory -- Preface / Raphals, Lisa -- Abbreviations -- Introduction -- 1. Chinese Accounts of Wisdom and Knowledge -- 2. Wisdom in Classical Confucianism -- 3. Mohist Knowledge -- 4. Taoist Wisdom -- 5. Cunning in Rhetoric and Strategy -- Interlude -- 6. The Strategies of Zhuge Liang -- 7. The Journey to the West -- 8. Heroes, Kings, and Kingmakers -- 9. Skillful Means -- 10. Conclusions -- Appendix 1. Warring States Terms for Wisdom and Cunning -- Appendix 2. Terms for Wisdom and Cunning in Two Ming Novels -- Appendix 3. Semantic Range -- Character List -- Selected Bibliography -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019).
Includes bibliographical references (pages 246-260) and index.
JSTOR
Keywords: Philosophy, Ancient; Philosophy, Chinese; Poetics -- History -- To 1500.; Philosophie ancienne; Philosophie chinoise; LITERARY CRITICISM -- Ancient & Classical; Philosophy, Ancient; Philosophy, Chinese; Poetics; Klugheit; Philosophie; Weisheit; Wissen; China; Griechenland; Cultuurgeschiedenis; Grieken; Oudheid; Wijsheid; Philosophie antique; Philosophie chinoise; To 1500; History